Hubungan Kompetensi Pedagogik Guru Terhadap Hasil Belajar Biologi Siswa Kelas X SMAN 3 Tualang Kabupaten Siak - Mayang Sari Ramadani; Nurul fauziah (UIR Press, 2023)
This study aims to find out how the teacher's pedagogic competence relates to the biology learning outcomes of class X SMAN 3 Tualang. This study is a particular kind of descriptive research, and the correlational method was employed. The study's sampling strategy included a saturated sampling technique. The correlation coefficient (rcount) for the data analysis, which has a significant level of 5%, is 0.69, placing the correlation in the low group. As a result of evaluating the obtained hypothesis, tcount (9.78) > ttable (1.97). This indicates that while Ho is accepted, Ha is not. then, based on the analysis's findings, the coefficient of determination is reached by 42%, whilst 58% are influenced by other variables or factors that affect student learning outcomes. This indicates that the pedagogic competency variable (X) contributes positively to the learning outcomes (Y) attained by students. The results of this study indicate that